Implementasi Sistem Mitigasi Risiko terhadap Keselamatan Praktikum Mahasiswa di Laboratorium Keperawatan: Literatur Review - Gaudentiana Un Bria; Rufinus Rame; Christina Anugrahini (Journal of Educational Innovation and Public Health, 2026)
The safety of student practicum activities in nursing laboratories is an important aspect of supporting a safe and effective learning process because laboratories have various potential hazards, such as injuries caused by practicum equipment, chemical exposure, electrical hazards, and inadequate safety facilities. This study aimed to analyze the implementation of risk mitigation systems for student practicum safety in nursing laboratories through a literature review method. The study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Article searches were conducted through Google Scholar, Proquest, and Cambridge databases using keywords related to laboratory safety, risk mitigation, occupational health and safety, and nursing laboratories. The inclusion criteria included research articles published between 2021–2026, written in Indonesian or English, and available in full text. The selection process resulted in 5 articles that met the criteria for analysis. The results of the literature review showed that laboratory practicum risks included injuries from sharp objects, burns, electric shocks, chemical exposure, and inadequate safety facilities such as fire extinguishers and ventilation systems. Risk mitigation implementation was carried out through risk identification, use of personal protective equipment, safety standard operating procedures, occupational health and safety training, and practicum supervision. The implementation of an optimal risk mitigation system can improve student safety and minimize work accidents in nursing laboratories.